LA OPCIÓN AUDIOVISUAL COMO ESTRATEGIA PARA LA REFLEXIÓN: UNA EXPERIENCIA ALTERNATIVA - Bustos Mora, Giselle (2023)
The experience of producing a video upon a theme related to sensitive and tough topics, such as the xenophobia and the refusal toward inmigrants, offers some valuable considerations for future initiatives on the producing alternative lines.In this brief, the intention is to think over the experience of producing “Objections to a nica (Nicaraguan) girlfriend” a drama documentary that invites to think deeply about the Costa Rican national identities and its link with the Nicaraguans.